Differences in Oral Structure and Tissue Interactions during Mouse vs. Human Palatogenesis: Implications for the Translation of Findings from Mice - Yu, Kai; Deng, Mei; Naluai-Cecchini, Theresa; Glass, Ian A.; Cox, Timothy C. (Frontiers in Physiology, 2017)
Clefting of the secondary palate is one of the most common human birth defects and results from failure of the palatal shelves to fuse during embryonic development. Palatogenesis is traditionally considered to be a highly conserved developmental process among mammalian species. However, cleft palate phenotypes in humans are considerably more variable than those seen in mice, the most common animal model for studying palatal development and pathogenesis of cleft palate. In this investigation, we utilized macroscopic observations, histology and 3D imaging techniques to directly compare palate morphology and the oral-nasal cavity during palate closure in mouse embryos and human conceptuses. We showed that mouse and human palates display distinct morphologies attributable to the structural differences of the oral-nasal cavity. We further showed that the palatal shelves interact differently with the primary palate and nasal septum in the hard palate region and with pharyngeal walls in the soft palate region during palate closure in mice and humans. Knowledge of these morphological differences is important for improved translation of findings in mouse models of human cleft lip/palate and, as such, should ultimately enhance our understanding of human palatal morphogenesis and the pathogenesis of cleft lip/palate in humans.